Performance of calcium lignosulfonate as a stabiliser of highly expansive clay - Fernandez, Mariano Tomás (2020)
The efficiency of calcium lignosulfonate (CLS) as an expansive soil stabiliser was studied. CLS is a bio-based polymer, obtained as a sub-product of the paper industry. Its use as a soil stabilizer not only enhances the properties of the soil but also eliminates the economic and environmental costs of its disposal. In this project, CLS was added to a natural smectite clay (Clay) from Comodoro Rivadavia, Argentina. Smectite clays exhibit significant plastic volumetric deformations when subjected to moisture variations. Clay was stabilised using 3.0 and 5.0% mass of CLS. The efficiency of CLS as a stabilising agent was measured studying its influence on the physical properties of Clay (Atterberg limits, Cation Exchange Capacity, Specific Surface Area). Considerable reductions of the cation exchange capacity (CEC) and the specific surface were registered. Furthermore, a full hydro-mechanical characterisation of Clay with CLS was performed in saturated and unsaturated conditions. Results from free swell and swelling pressure tests show that CLS reduces by nearly a half and nearly a quarter the free swell and swelling pressure of Clay, respectively. Additionally, mercury intrusion porosimetry (MIP) and scanning electron microscopy (SEM) tests were carried out to evaluate the microstructure re-arrangement of Clay when CLS was added. Results showed that a relatively small amount of CLS might yield a reasonably satisfactory performance as a stabiliser, particularly in reducing the natural Clay's swelling potential. Moreover, CLS induced an increase in the stiffness and strain at failure of Clay and a reduction in its porosity.